TERMINOLOGICAL ANALYSIS OF THE POPULATION MIGRATION PROCESS - Saipova Malaxat (TADQIQOTLAR, 2025)
Annotation. The article examines the development of population migration and lists the stages of this process as proposed by scholars. Additionally, it analyzes definitions of the term "migration" provided by both domestic and foreign researchers and presents the author’s own definition.